The Actuality of the Strategy of Human Resources Employment in the Ministry of Youth and Sports, Department of the Matters of the Regions and Cities - Dr. Mohammad Q. Mohammad; Naser, Abduljaleel Jabbar; Hussein, Hussein Khmais (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this research were to design a standard to recognize the reality of employing human resources in the Ministry of Youth and Sports, Department of the Matters of the Regions and Cities. It focuses on the current methods and presents a set of solutions and recommendations based on the results of this study. Total Number of The Sample was 245, divided in to four groups: pilot study sample was 5, the Structure Sample was 80, the Rationing Sample was 100 and the Implementation Sample was 60. This study found that The political situation and the change of administrations affect the gathering of the human resources. And the current mechanism used by the Ministry in the process of accepting candidates for the job do not help in motivating the workers to improve their skills and administrative abilities. as well as this study indicates that the procedures of the Ministry are not the only responsible for having an effective system of employment.